AN EXPERIMENTAL EVALUATION OF THE EFFECT OF RUDRAKSHA (ELAEOCARPUS GANITRUS ROXB) IN ADRENALINE AND NICOTINE INDUCED HYPERTENSION - Sarma, Jayantha Kumar (Medknow Publications & Media Pvt Ltd, 2004)
This study highlights the effect of Rudraksha (Elaeocarpus ganitrus Roxb) in experimentally induced acute hypertension by adrenaline and nicotine. Study was done in 6 anaesthetised cats having similar body weight and age. 90 % Ethanol extracts of Elaeocarpus ganitrus Roxb was given intravenously to cats. Blood pressure was measured by using Pressure transducer and Polyrite (INCO). Elaeocarpus ganitrus (Roxb) reduces adrenaline induced hypertension and also normal blood pressure; but it is not effective in nicotine induced hypertension. The effect of the drug was found when the water soluble portion of the extract was given to cats in a dose of 15mg / kg body weight.